Fighting fire with fire: target audience responses to online anti-violence campaigns - Roslyn Richardson
With the Syrian civil war entering its third year, drawing an increasing number of young Westerners into the fray, this report sought to discover how audiences respond to government-sponsored and community-generated online efforts to counter violent extremism. Overview Prepared by the Australian Strategic Policy Institute under contract to New South Wales Police Force and funded by Australia-New Zealand Counter-Terrorism Committee (ANZCTC). As the Syrian civil war entered its third year, drawing an increasing number of young Westerners into the fray, ASPI spoke with young Muslim Sydneysiders about Australia’s online efforts in countering violent extremism (CVE). This report sought to discover how such audiences respond to government-sponsored and community-generated anti-violence campaigns. The summary report outlines the main findings and recommendations from the full report. On the whole this report challenges approaches that only discuss Muslim youth as being highly vulnerable and in dire need of empowerment to resist violent propaganda. Instead, it shows that some have taken a lead role in challenging violent narratives and are empowering themselves. This report is intended for use by government agencies and communities to inform their future work in this area. Appendix 2 in the full report, by Kristy Bryden, considers international approaches to countering violent narratives online, particularly those developed by the UK, the US, Denmark, Canada and the Netherlands